Cytological Analysis Of Female Patients With Sigmoidal Colpopoiesis Depending On The Duration Of Operation (Open Herald: Periodical of Methodical Research, 2024)
The aim of the study is to study the cytological characteristics of the sigmoid colon after vaginoplasty in women of different periods.